Athlete mental health in the Olympic/Paralympic quadrennium: a multi-societal consensus statement - Henriksen, K.; Schinke, R.; McCann, S.; Durand-Bush, N.; Moesch, K.; Parham, W. D.; Hvid Larsen, C.; Cogan, K.; Donaldson, A.; Poczwardowski, A.; Noce, F.; Hunziker, J. (International Journal of Sport and Exercise Psychology, 2020)
This consensus statement is the product of the Second International Think Tank on Athlete Mental Health, held on the initiative of the International Society of Sport Psychology. The purposes of the Think Tank were to engage international sport psychology societies and organisations in a discussion about athlete mental health as embedded in an Olympic/Paralympic cycle, and to develop practical recommendations for sport organisations. An invited group of designated experts discussed applied experiences working with athletes within an Olympic and Paralympic environment. The Games and mental health are interrelated, because athletes committing whole-heartedly to an Olympic/Paralympic pursuit are at increased risk of disappointment, identity foreclosure, and high life stress. Dividing the quadrennial into three main phases (i.e., pre-, during-, and post-Games) participants discussed three topics for each phase: (1) the key opportunities and challenges; (2) the sport environment, and how it can nourish or malnourish athlete mental health; and (3) collaboration and communication within expert support teams. Each phase of the quadrennium presents specific challenges and opportunities, and mental health screening and support should be administered across all phases. However, the post-Games period is one of increased vulnerability, while at the same time, the returning staff is oftentimes exhausted and unavailable. Ideally, a specialised collaborative team should handle the post-Games mental health support. Initiatives are needed to (a) improve the psychological safety of pre-, during-, and post-Games high performance environments, (b) reduce unnecessary stress, (c) optimise recovery, (d) de-stigmatize mental health issues, and (e) increase help-seeking.